Pleistocene Non-Marine Mollusca of the Gatineau Valley and Ottawa Areas of Quebec and Ontario, Canada - Edwin David Bickel (Hello World!, 1970)
Fifty-five species and forms of land and freshwater mollusks were recovered from seven Late Wisconsin marl deposites in the Gatineau and Ottawa Valleys of Quebec and Ontario. Vertical samples were taken through marl beds and associated lacustrine sediments at four deposits, three in the Gatineau Valley and one in the city of Ottawa, and vertical changes in the relative abundance of mollusk species are reported. Two deposits in the Gatineau Valley and one in the Ottawa area are represented by single grab samples.